Product Awareness of International Muslim Students in South Korea about the Importance of Halal Food - Narariya Handani (Publindo Akademika, 2021)
The objective of this study was to obtain the views of muslim international student about importance of halal food. This study was conducted in South Korean cities having muslim international students. The research design used was qualitative conducted with interview and field study with participant sample of international students in South Korea. The results showed the key themes explanation of halal food, importance of halal food, halal food price. More specifically, the results presented that among all students answer that they must eat halal food. They have to eat halal food as in rules in their religious tenet. Besides that, this was is considered not just because of the rule, but also purposing their healthy, where they highly perceive that halal food also mean hygienic food. From the discussion, it can be concluded that even the halal price is expensive, and it is not a big deal for muslim. They will buy it even it’s expensive. The results practically useful for local and international marketers to assess their marketing to muslim consumer in non-muslim countries as it will be good opportunity for marketers to gain some profit by sell halal food and increasing the product price.